SANS characterization of porous magnesium for hydrogen storage - Gil Posada, Jorge Omar; Hall, Peter J. (International journal of hydrogen energy, 2014)
Porous magnesium was produced through the thermal decomposition of various additives in an effort to increase hydrogen storage capacity. Samples were characterized using SANS and different theoretical models were applied to the results and discussed. The polydisperse self-assembled (PSA) model was found to best represent the scattering from these materials as this model incorporates the polydispersity of the pores and allows for variations in structure factor. Pure magnesium produced using the same thermal method absorbed a negligible amount of hydrogen, and hydrogen uptake was found to increase with increasing porosity as determined using the PSA model. Maximum hydrogen uptake (1.3%) was found when 0.3% Cs2CO3 and 0.5% Ni were combined as an additive during thermal treatment. In addition, the development of porosity was found to promote hydrogen desorption at lower temperatures. SANS represents an indispensible method by which to characterize materials and the PSA model described in this work has the potential to be extremely useful in the characterisation of porous metallic systems. [Display omitted] •We found that porous magnesium could store up to 1.3% hydrogen.•We found that the PSA model provides a realistic insight of porous magnesium.•We show that the amount of hydrogen uptake correlates with the micropore volume.•We show that porosity in magnesium should be characterised using polydisperse models.